Early Postnatal Comprehensive Biomarkers Cannot Identify Extremely Preterm Infants at Risk of Developing Necrotizing Enterocolitis - Hoffsten, Alice; Markasz, Laszlo; Lilja, Helene Engstrand; Olsson, Karl Wilhelm; Sindelar, Richard (Frontiers in Pediatrics, 2021)
BACKGROUND: Necrotizing enterocolitis (NEC) is a fatal disease where current diagnostic tools are insufficient for preventing NEC. Early predictive biomarkers could be beneficial in identifying infants at high risk of developing NEC. OBJECTIVE: To explore early biomarkers for predicting NEC in extremely preterm infants (EPI). METHODS: Blood samples were collected on day 2 (median 1.7; range 1.5-2.0) from 40 EPI (median 25 gestational weeks; range 22-27): 11 developed NEC and 29 did not (Controls). In each infant, 189 inflammatory, oncological and vascular proteomic biomarkers were quantified through Proximity Extension Assay. Biomarker expression and clinical data were compared between the NEC-group and Controls. Based on biomarker differences, Controls were sorted automatically into three sub-groups (1, 2 and 3) by a two-dimensional hierarchical clustering analysis. RESULTS: None of the biomarkers differed in expression between all Controls and the NEC-group. Two biomarkers were higher in Control 1 and 16 biomarkers were lower in Control group 2 compared to the NEC-group. No biomarker distinguished Control 3 from the NEC-group. Perinatal data were similar in the whole population. CONCLUSIONS: Early postnatal comprehensive biomarkers do not identify EPIs at risk of developing NEC in our study. Future studies of predictors of NEC should include sequential analysis of comprehensive proteomic markers in large cohorts.